Salt Recovery from the Hot Treated Aluminium Melting Dross Residue - Hegedüs, Balázs; Nagy, Gábor; Kékesi, Tamás (Hungarian materials and chemical sciences and engineering (Online), 2023)
In the aluminium industry, the large amount of dross – a by-product of scrap melting – is usually further processed at high temperature re-melting to reclaim the high metallic content entrapped in material. The residue of the hot dross treatment is mainly composed of oxides, and chloride salts from the flux added during the thermo-mechanical process. The major NaCl and KCl components of the added salt are removed by a technically simple leaching process, however, the brine must be treated to remove the dissolved chlorides. We have investigated the energy requirement and efficiency of the evaporation procedure with a simple vessel of insulated walls and submerged heater. The specific heat capacity of the examined NaCl/KCl saturated solution of 2 : 1 mass ratio was determined as ~3155 J/kgK and the latent heat as 1538 J/kgK. The heat efficiency obtained with the system at room temperature initially was found to approach a 97% level as stable conditions were reached. The crystallized NaCl/KCl salt mixture – with possible modifications of it composition – can be recycled to the furnace.